(untitled) (American Journal of Islam and Society, 2006)
Orientalsim and postcoloniality are synonymous with contemporary culture and literature. As much as the younger generations of formally colonized nations and communities would like to argue, the truth of the matter is that on some level, their colonial times have made an everlasting impression on their own identity and culture. This was one of the many themes that the conference, held at the Södertörns Högskola University College in Stockholm, Sweden, focused on during its congested four-day program. This was one of the largest gatherings to deal with issues of ethnic identity and diversity, as well as the non-proverbial influences of colonialism in the reshaping of new communities and their modernized cultures. Papers presented ranged from diversity and nationalism in the postcolonial context, postcolonialsim and religious studies, African-American writing and social activism, colonial romanticism and white supremacy, and postcolonial literature and film in English, among other topics ...